NITROGEN CONCENTRATION IN CORAL REEF: THE CONTRIBUTION OF CORAL FORMS AND NITROGEN FIXING BACTERIA IN KARIMUNJAWA ISLANDS - Suryanti Suryanti; Supriharyono Supriharyono; Sigit Febrianto; Muslidin Aini (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2020)
Coral is an ecosystem in the coastal area which plays an important role in controlling nutrient cycle in the sea. This research aimed to study the the nitrogen concentration in coral and to analyze the influence of nitrogen fixing bacteria on the concentration of nitrogen in coral. The research was carried out by field observation, by taking coral reef samples and analyzed in the laboratory for its nitrogen concentration and number of nitrogen fixing bacteria. Data analysis was carried out by ANOVA and regression. The analysis resulted that there was a significant difference of nitrogen concentration in massive and branching corals. However, there is no significant correlation between the sampling location and types of coral on the density of nitrogen fixing bacteria, both Nitrosomonas sp. and Nitrobacter sp. Regression analysis showed that the concentration of nitrogen in coral tissue was not significantly related to the density of nitrogen fixing bacteria. The result of this research implies that the concentration of nitrogen in the coral tissue may be affected by many other factors.